PKM Perangkat Media Gamifikasi Untuk Layanan Bimbingan Dan Konseling Bagi MGBK - Abdul Saman; Nur Fadillah Umar; Muhammad Ilham Bakhtiar; Akhmad Harum (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2022)
. This PKM aims to train participants to use BK Service Media through Information Technology (ICT); (2) to provide an understanding of using gamification media in Guidance and Counseling services; (3) So that BK teachers make BK services interesting, and fun by integrating technology devices. External targets are service devices that use LMS applications, Kahoot applications, Quiziz, Wordwell, and padlets. The methods used are lectures, practice, question and answer, and assistance in making gamification media. The results of the PKM are (1) Gamification Media Training for Guidance and Counseling services is carried out offline, and practiced using the media application. Gamification media used in counseling service activities are the Lmerning management system application, Kahoot application, Quizis, Mentimer application, and Wordwall. The use of Gamification Media gives enthusiasm to participants, especially as participants who take part in gamification practices to get badges or awards from the final results of gamification practices, enthusiasm and motivation to follow practice steps including active participation as illustrated by students whose goal is to increase points and badges from the training activities that are followed ; (2) From the results of the training it shows the level of usefulness and the impact is very large on the participants or is in the average of 93%. It is described that Participants have been able to create media service devices using the gamification media application, including making them according to their needs and the types of services to be provided